Analysis & Evaluation of the Reality of Environmental Accounting in Industrial Companies - A Case study of the National Company of Phosphate Mines (Somiphos)- Tebessa - Wieme, MELLAH; AMAMRA Yasmina , AMAMRA Yasmina (Milev Journal of Research and Studies, 2020)
The objective of the research is to analyze and assess the reality of the application of environmental accounting in the Algerian industrial establishments based on the extractive industry. As a result of the environmental damage and pollution caused by the environmental accounting application to preserve the environment and support the sustainability of development, the accounting standards of environmental activity through accounting disclosure and measurement Environmental costs. The research found that there are environmental pollution costs incurred by the Phosphate Mines Foundation, but the accounting disclosure of environmental activities is still in its early stages due to the absence of financial and technical data on pollution